Atypical Focal Osteomyelitis as Initial Manifestation of AIDS - A. Akiki; Y. Bilde (Case Reports in Orthopedics)
Persistent pain development after a skeletal contusion rarely poses the diagnosis of osteomyelitis. We report the case of a fibular head contusion as an initial manifestation of a focal abscess development in a healthy young patient. The traditional treatment of surgical drainage revealed the presence of an atypical Mycobacterium haemophilum isolates in the abscess. This lead to further investigations that concluded and established the diagnosis of AIDS. Conclusion. Isolation of an atypical Mycobacterium haemophilum in any abscess should lead the physician to accomplish further investigations and look for AIDS even in young healthy subjects.